Parsing the functions of immediate-early proteins in the lytic–latent balance of HCMV infection - Yaarit Kitsberg; Aharon Nachshon; Alexander Brandis; Tevie Mehlman; Noam Stern-Ginossar; Michal Schwartz (Proceedings of the National Academy of Sciences, 2026)
Human cytomegalovirus (HCMV) establishes lifelong latency, during which immediate-early (IE) gene expression is strongly repressed. IE1 and IE2 are considered master regulators of the lytic cycle, yet it remains unclear whether their expression levels are sufficient to determine infection outcome, defined here as the balance between lytic and latent infection, and which viral or cellular processes underpin this control. Here, we show that when viral entry is enhanced in monocytes, overexpression of either IE1 or IE2 significantly increases lytic replication, identifying their abundance as a critical barrier governing infection outcome. Mechanistic analysis reveals that these effects of IE1 and IE2 are mainly mediated through two distinct modes of host manipulation. IE1 promotes disruption of PML bodies, thereby facilitating a broad increase of viral gene expression, whereas IE2 elevates cellular dNTP pools and creates an environment permissive for viral DNA replication, consistent with two key limiting barriers to the initiation of lytic replication. Notably, induction of IE1 in latently infected cells is also sufficient to promote reactivation of viral gene expression. Together, these findings define the limiting functions of IE1 and IE2 in overcoming host-imposed barriers to lytic replication and reactivation.